不失一般性地设:(cosA)^2+(cosB)^2+(cosC)^2=(sinC)^2,则:
(cosA)^2+(cosB)^2+2(cosC)^2=1,
∴2(cosA)^2+2(cosB)^2+4(cosC)^2=2,
∴[2(cosA)^2-1]+[2(cosB)^2-1]+2(cosC)^2=-2(cosC)^2,
∴cos2A+cos2B+2(cosC)^2=-2(cosC)^2,
∴2cos(A+B)cos(A-B)+2[cos(A+B)]^2=-2(cosC)^2,
∴2cos(A+B)[cos(A+B)+cos(A-B)]=-2(cosC)^2,
∴-2cosC(2cosAcosB)=-2(cosC)^2,
∴2cosAcosB=cosC,
∴2sinCcosAcosB=sinCcosC,
∴2(sinC/cosC)cosAcosB=sinC,
∴2tanCcosAcosB=sin(A+B),
∴2tanCcosAcosB=sinAcosB+cosAsinB,
∴2tanC=(sinA/cosA)+(sinB/cosB),
∴2tanC=tanA+tanB,
∴tanA、tanC、tanB组成一个等差数列.
同理可证:
(cosA)^2+(cosB)^2+(cosC)^2=(sinA)^2 时,tanB、tanA、tanC成等差数列.
(cosA)^2+(cosB)^2+(cosC)^2=(sinB)^2 时,tanA、tanB、tanC成等差数列.